2013
DOI: 10.1038/bjc.2013.342
|View full text |Cite
|
Sign up to set email alerts
|

Statin use in primary inflammatory breast cancer: a cohort study

Abstract: Background:Some studies have suggested that statins, which have cholesterol-lowering and anti-inflammatory properties, may have antitumor effects. Effects of statins on inflammatory breast cancer (IBC) have never been studied.Methods:We reviewed 723 patients diagnosed with primary IBC in 1995–2011 and treated at The University of Texas MD Anderson Cancer Center. Statin users were defined as being on statins at the initial evaluation. Based on Ahern et al's statin classification (JNCI, 2011), clinical outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 40 publications
4
79
1
Order By: Relevance
“…Two previous studies performed meta-analyses but suffered obvious limitations in terms of an insufficient number of included studies and the lack of unified end points [8,9]. Some articles have previously shown that different statin types may have different effects on breast cancer incidence [3][4][5] and prognosis [5,[10][11][12]19]. Thus, we preformed the current meta-analysis using mortality as the unified end point; moreover, we sought to explore the different influences of statin types and different follow-up times on the prognosis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies performed meta-analyses but suffered obvious limitations in terms of an insufficient number of included studies and the lack of unified end points [8,9]. Some articles have previously shown that different statin types may have different effects on breast cancer incidence [3][4][5] and prognosis [5,[10][11][12]19]. Thus, we preformed the current meta-analysis using mortality as the unified end point; moreover, we sought to explore the different influences of statin types and different follow-up times on the prognosis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Statin use was found to be associated with increased overall DFS, in line with previous studies exploring the impact of statin use in breast cancer patients. 28,[33][34][35][36] Pre-or postdiagnosis statin studies have already shown a beneficial effect on survival 34,36 but not all of them. 28,33,35 Even in the latter case, where the studies showed no effect on survival, subgroups revealed any significant beneficial correlations; however, the number of patients in each subgroup was too small to draw definite conclusions, and the results should be interpreted with extreme caution.…”
Section: Discussionmentioning
confidence: 99%
“…A review of 723 patients diagnosed with primary inflammatory breast cancer in 1995-2011 showed that hydrophilic statins were associated with significantly improved progression-free survival (PFS) rates (47). However, long-term use of statins was associated with increased risk of invasive ductal carcinoma (IdC; n=916) and invasive lobular carcinoma (ILC; n=1,068) in a contemporary population-based case-control study conducted in the Seattle-Puget Sound region.…”
Section: Lovastatinmentioning
confidence: 99%